Strategies to Increase Financial Literacy, Deposit Guarantee Programs, Quality of Service from Interest in Savings Post the Covid 19 Pandemic - Ni Wayan Dian Irmayani (Prosiding Seminar Nasional Ilmu Manajemen, Ekonomi, Keuangan dan Bisnis, 2023)
The Covid-19 pandemic has caused job losses and an economic downturn, requiring strategies to overcome financial challenges. Encouraging a culture of saving from an early age provides many benefits, including instilling discipline, fostering a mindful attitude towards money, and preventing excessive consumption. Financial literacy is essential for avoiding financial problems that arise from low incomes and mismanagement, such as credit abuse and lack of financial planning. Recognizing the importance of financial literacy, this study aims to increase knowledge about deposit insurance programs to improve saving decisions. In addition, improving service quality plays an important role in attracting customers and ensuring success. This study uses primary data obtained from questionnaires distributed to BPR customers in Bali. This study uses qualitative data analysis which includes validity and reliability tests, normality and linearity tests, multicollinearity tests, and heteroscedasticity tests. Regression analysis and multiple linear analysis were used for data analysis.